Chronic Hepatitis with Liver Granulomas in a Patient with Granuloma Annulare: A Case Report and Review of the Literature - Majid Alsahafi; Mohammed I. AlJasser; Sunil Kalia; H. M. Yang; Alnoor Ramji (Case Reports in Gastrointestinal Medicine)
Granuloma annulare (GA) is a benign granulomatous skin disorder of unknown etiology. GA is rarely associated with liver diseases. We report a unique case of chronic hepatitis with liver granulomas in a patient with GA. Despite an extensive workup, no clear etiology for the hepatitis was found. Based on the possible immune pathophysiology of GA and the presence of liver granulomas, the patient was treated with prednisone and azathioprine which resulted in complete normalization of the liver enzymes and concurrent improvement of GA. The association between liver diseases and GA is reviewed.